Minimum Wages and Welfare of Private Lecturers in Indonesia: Perspectives of Islamic Law and Positive Law - Ahyani, Hisam; Muharir, Muharir; Khairuddin, Khairuddin; Rahman, Encep Taufik; Wibowo, Dwi Edi; Ulummudin, Ulummudin; Abduloh, Agus Yosep; Kuncoro, Irfan; Lousada, Sérgio António Neves (Yayasan Abdurrauf Cendekia Nusantara, 2025)
This study examines the welfare issues of private university lecturers in Indonesia who receive substandard wages, by analyzing them through the perspectives of Islamic law and positive law. The objective of this paper is to explore the alignment between the principles of wage justice in Islamic law and the wage regulations within the national legal framework, especially concerning employment in the private higher education sector. The methodology employed is normative juridical with a qualitative analysis of legal documents and Islamic legal literature. The findings indicate that private lecturers are employed under contractual agreements subject to labor regulations, which often fail to provide adequate welfare guarantees. On the other hand, Islamic law emphasizes justice, fairness, and certainty in wage distribution as part of workers' rights protection. The main novelty of this study lies in identifying the gap between the normative ideals of Islamic law and the practical enforcement of positive law in the higher education context. The impact of this research is to propose an integrative legal approach that incorporates Islamic ethical values into wage regulation policies, aiming to improve the socio-economic well-being of academic professionals in Indonesia. Abstrak: Penelitian ini mengkaji permasalahan kesejahteraan dosen perguruan tinggi swasta (PTS) di Indonesia yang menerima upah di bawah standar, dengan meninjau dari perspektif hukum Islam dan hukum positif. Tujuan dari studi ini adalah untuk menggali kesesuaian prinsip-prinsip keadilan upah dalam hukum Islam dengan pengaturan pengupahan dalam sistem hukum nasional, khususnya terhadap tenaga kerja di sektor pendidikan tinggi swasta. Metodologi yang digunakan dalam penelitian ini adalah pendekatan yuridis normatif dengan analisis kualitatif terhadap dokumen hukum dan literatur keislaman. Hasil kajian menunjukkan bahwa dosen PTS memiliki status hubungan kerja berdasarkan perjanjian kerja yang tunduk pada aturan ketenagakerjaan, yang dalam praktiknya belum memberikan jaminan kesejahteraan yang memadai. Sementara itu, hukum Islam menekankan keadilan, kelayakan, dan kepastian dalam pemberian upah sebagai bagian dari perlindungan hak pekerja. Temuan utama dari penelitian ini menunjukkan adanya kesenjangan antara idealisme hukum Islam dan implementasi hukum positif di sektor pendidikan tinggi. Studi ini memberikan kontribusi dengan menawarkan pendekatan integratif antara hukum Islam dan hukum ketenagakerjaan untuk mendorong formulasi kebijakan pengupahan yang lebih adil dan berorientasi pada kesejahteraan akademisi di Indonesia. Kata kunci: hukum Islam; hukum ketenagakerjaan; kesejahteraan dosen; perguruan tinggi swasta; upah minimum